Densely integrated Co, N-Codoped Graphene@Carbon nanotube porous hybrids for high-performance lithium-sulfur batteries. (August 2019) - Cheng, Dongdong; Zhao, Yelin; Tang, Xingwei; An, Tong; Wang, Xin; Zhou, Han; Zhang, Di; Fan, Tongxiang
Abstract: Design and synthesis of multifunctional sulfur hosts with comprehensively addressed conductivity, porosity and polarity is vital but challenging in the development of high-performance lithium-sulfur batteries. In this work, densely integrated Co, N-codoped graphene@carbon nanotubes porous hybrids (Co, N-G@CNT) are prepared as high-efficiency sulfur hosts for lithium sulfur batteries via reductive pyrolysis of (Co, Zn)-bimetallic zeolitic imidazolate frameworks separated graphene oxide sheets. The obtained Co, N-G@CNT possesses 3D interconnected conductive network, large nanopore volume and high accessible surface area as well as enriched doping sites, which endow the carbon matrix multifaceted abilities for sulfur accommodation and electron/ion transfer as well as polysulfides immobilization. Due to the rational structure design of the host material, the Co, N-G@CNT/S composite exhibits high sulfur utilization (1398 mA h g −1 at 0.2C), excellent rate capability (611 mA h g −1 at 6 C) as well as remarkable cycling stability (retained 659 mA h g −1 at 1C after 1500 cycles). This work provides a new perspective to function-directed structure design of sulfur hosts for lithium-sulfur batteries, and also holds great promise for the application in other energy storage/conversion systems such as metal air batteries, supercapacitors, and electrochemical catalysts. Graphical abstract: Image 1